The Influence of the School English Community on Students’ Speaking Ability at SMAN 1 Pinrang - Hartawan, Hari; Muhayyang, Maemuna; Baa, Sultan (Journal of Excellence in English Language Education, 2025)
This study aims to find out whether or not the School English Community has any influence on the speaking abilities of students at SMAN 1 Pinrang. Employing a quantitative research method. The primary objective is to quantify the relationship between participation in the English community and improvements in students' speaking skills. A Likert scale questionnaire was administered to a sample of 20 students, comprising both active members of the English community and those not involved in the community. The speaking test measured variables such as accuracy, fluency, and comprehensibility. Data analysis involved descriptive statistics to determine the strength and significance of the relationship between engagement in the English community and speaking ability. The research results show that the English community influences student speaking ability. Students who were more involved in community activities exhibited higher levels of confidence, better fluency, more accurate vocabulary usage, and improved pronunciation compared to their peers who were not active in the community. It can be seen from the result of the speaking test that the average score of the students who joined the English community was a little bit higher than that of the students who did not. In conclusion, the English community can influence students’ speaking ability at SMAN 1 Pinrang.